Mapuche Demands during Educational Reform, the Penguin Revolution and the Chilean Winter of Discontent. (December 2013) - Webb, Andrew; Radcliffe, Sarah
Abstract Enduring inequalities in Chile's education system are both a socio‐economic and ethno‐national problem. Student protests in 2006 and 2011 are representative of growing public concerns over the neoliberal socio‐economic model adopted by respective governments since the military regime ended in 1990. Education has also become a contested space in which the recognition of indigenous rights – and cultural and linguistic diversity in particular – have been negotiated. This article presents an analysis of the history of Mapuche struggles over education, in light of recent neoliberal reforms and political protests. Reforms to address large achievement differentials among indigenous populations have come through proposals for Intercultural Bilingual Education (IBE) in Chile and these, we suggest, have challenged the hegemonic education system and its assimilatory mechanisms. Its current administration, however, reflects minimal commitments to indigenous rights and only the thinnest recognition of cultural difference. Instead, the status quo of mono‐cultural and mono‐linguistic Chilean nationalism continues to be transmitted via the national curriculum.